CORPORATE TAX STRATEGY, RISK, AND LONG-TERM VALUE CREATION: INSIGHTS FROM TECHNOLOGY, PHARMACEUTICAL, AND MANUFACTURING SECTORS (Contemporary Journal of Social Science Review, 2025)
This study quantifies the impact of corporate tax policies on shareholder equity with a particular focus on the role of effective tax planning, potential violations, and the overall value of firm operations. A descriptive–correlational research design was adopted, drawing on the theoretical foundations of agency theory, stakeholder theory, and legitimacy theory. The analysis was conducted on 150 multinational corporations operating in the technology, pharmaceutical, and manufacturing sectors over the period 2018 to 2023. Panel data regression results demonstrate a significant negative association between the effective tax rate and firm value. This finding explains that tax-minimizing strategies contribute positively to firm valuation. However, the study further reveals that the benefits of stratified effective tax rate strategies can only be sustained in the long run under conditions of strong governance structures. Firms with well-developed governance systems, including independent boards of directors and robust audit and control mechanisms, were able to mitigate the reputational and regulatory risks typically associated with aggressive tax minimization. An industry-level analysis highlights that the technology sector, which relies heavily on intangible assets, faces stricter regulatory scrutiny and correspondingly higher risk exposure. The evidence indicates that while tax relocations and planning strategies may enhance short-term shareholder value, unethical practices or deviations from regulatory standards compromise long-term sustainability. The study concludes that there is a pressing need for transparent, stakeholder-oriented, and well-regulated taxation practices. By embedding such practices into corporate governance frameworks, firms can achieve a balance between maximizing shareholder value and ensuring compliance with ethical and legal expectations. That would present a sustainable value creation that is suitable for the managers and policymakers.